The Effect of HCM Practices and HRM Development and Islamic Economics as Mediation on Employee Commitment in Purwakarta Regency - Eti Jumiati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This paper examines the “effect of human capital management practices and HRM Development and the Islamic economics as mediation on evaluating the role of mediation in human resources management and employee commitment in several companies in Purwakarta Regency.Design/Method/Approach: This research uses quantitative research methods. The analysis technique used is path analysis or SEM (Structural Equation Modeling) which is operated with the Smart PLS 3.0 application. The samples used were 75 respondents who were taken randomly from several companies in Purwakarta Regency. Testing begins with validity and reliability tests. Followed by Confirmatory Analysis Test and SEM Processing with Smart PLS. Citation using Zotero.Findings: The HCM variable does not directly affect employee commitment by 0.518 < 1.96, so the null hypothesis is accepted and hypothesis 1 is rejected. So the HRM variable has a direct effect on employee commitment of 1.755 > 1.96, so the null hypothesis is rejected and hypothesis 1 is accepted. Islamic economic variables have a direct effect on employee commitment of 2.801 > 1.96, so the null hypothesis is rejected and hypothesis 1 is accepted. And the HCM variable has no indirect effect, namely through sharia economics on employee commitment of 1.814 < 1.96. So the HRM variable has an indirect effect, namely through sharia economics on employee commitment of 2,333 > 1.96Originality/Value: The main contribution of this research is to provide input to employees that human capital management combined with Islamic economics will have an impact on HR development.